Assessment of carbon greenhouse gas emissions from Patagonian inland waters affected by beaver impoundments - (:unkn) unknown (My University, 2025)
Although inland waters are important sources of methane (CH4) and carbon dioxide (CO2) to the atmosphere,there are few estimations in the world. In general, scientific community is encouraging to reduce uncertaintiesin those estimations, since inland waters seem contribute in major proportion as we had estimated. Forexample, CH4 contribution was readjusted from 6% in 2009 to 17% in 2016, from inland waters as naturalsource. Several reasons are explaining this dramatical discrepancy, but the most commons are related tonew data information is included, global warming increase emissions and anthropogenic activities areaffecting more ecosystems. The latter, is reflected currently in the introduction of 20 individual beavers inthe pristine wilderness of Southern Patagonia in 1946 (in Tierra del Fuego Island). Since their introduction,the population has been growing dramatically (ca. 95000 to 168000 individuals) and spreading to otherregions as Cape Horn and the continent land (region close to Punta Arenas city). Beaver is causing importantchanges in the ecosystems affected by building impoundments in this pristine area, affecting around of 3.6to 8.4% of the surface area of Tierra del Fuego, parts of Cape Horn and begging to settle in the continent.Therefore, it is expected that beaver activities affect directly the carbon cycling from inland waters and soilecosystems (by flooding soil area) of this pristine area. This proposal pretends to study beaver impoundmentbiogeochemical effect on the carbon cycling in the Magellanic sub-Antarctic Ecoregion with a rigorous effortin measuring CH4 and CO2 emissions and organic carbon mineralization. This proposal is with the intentionto take into account the myriad of carbon greenhouse gas emissions provoked by the disturbance ofintroduction of beaver in the unique wilderness endemic area between 47°S and 56°S in the Earth.